JOURNAL OF GOVERNMENT & POLITICS : The Conflict of Forest Tenure and the Emergence of Community Based Forest Management in Indonesia - Eko Priyo Purnomo , P.B Anand (FISIPOL UMY, 2014)
The forest tenure policy remains a controversy in Indonesia specially, on the issues of how to maintain forest on sustainable way and at the same time how to share of benefit of forest resources to the local communities.